Trade Policy and Market Power: Firm-level Evidence - Alan Asprilla; Nicolas Berman; Olivier Cadot; Melise Jaud (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This paper identifies the effect of trade policy on market power through new data and a new identication strategy. We use a large dataset containing export values and quantities by product and destination for all exporting firms in 12 developing and emerging countries over several years, merged with destination-product specific information on tariffs and non-tariff barriers. We identify market power by observing how exporting firms price discriminate across markets in reaction to variations in bilateral exchange rates. Pricing-to-market is prevalent in all regions of our sample, even among small firms, although it is increasing in firm size, in accordance with theory. More importantly, we find that the effect of non-tariff measures is not isomorphic to that of tariffs: the pricing-to-market behavior we observe suggests that, while tariffs reduce the market power of foreign firms through classic rent-shifting effects, non-tariff measures alter market structure and reinforce the market power of non-exiting firms, domestic and foreign ones alike. Keywords: Trade policy, non-tariff measures, tariffs, exchange rate, price discrimination
Keywords: F12; F13; F14; D40; F31; 330; trade policy; non-tariff measures; tariffs; exchange rate; price discrimination